2022
DOI: 10.21500/20112084.5263
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Perceived Social Support, Illness Perception, Life Orientation, Life Satisfaction, and Quality of Life Within a Sample of Cancer Patients

Abstract: Introduction: The impact of cancer represents a severe crisis for both patients and relatives. The implications of social support on well-being were well studied but several classifications have been proposed. Objective: The present cross-sectional study was aimed at examining the association between perceived social support (PSS) from family, friends, and significant other and psychological well-being (illness perception, life orientation, life satisfaction, and quality of life). Method: Participants were 138… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The findings showed that the family is the biggest source of support for the patients and friends and neighbors were in the next ranks, these results have been confirmed in other studies as well [30,31] which can indicate the lack of social support and in Indeed, there is a lack of palliative care, and part of the educational intervention of this research was to introduce existing support resources such as peer groups and relevant NGOs to cover this gap.…”
Section: Resultssupporting
confidence: 82%
“…The findings showed that the family is the biggest source of support for the patients and friends and neighbors were in the next ranks, these results have been confirmed in other studies as well [30,31] which can indicate the lack of social support and in Indeed, there is a lack of palliative care, and part of the educational intervention of this research was to introduce existing support resources such as peer groups and relevant NGOs to cover this gap.…”
Section: Resultssupporting
confidence: 82%
“…According to Ding et al (2023), better perceived social support contributed to a positive illness perception in their cross-sectional study. In addition, social support is positively associated with not only illness perceptions but also life satisfaction and quality of life (Faraci & Bottaro, 2022). According to previous studies, and in line with our results, individuals who perceived better social support were likely to have a more positive view of their illness/injury.…”
Section: Discussionmentioning
confidence: 99%
“…Social support could promote self-protection, alleviate individual mental health problems (e.g., anxiety and depression), and increase an individual's subjective well-being (Al-Dwaikat et al, 2022;Ozbay et al, 2007;Shumaker & Brownell, 1984). Although social support has been shown in other populations to help reduce anxiety, and depressive symptoms, manage emotions, promote positive body image cognition, and improve well-being (Al-Dwaikat et al, 2022;Faraci & Bottaro, 2022;, there are few studies in women with PCOS. This study revealed that women with PCOS in the Complete Mental Health profile received more social support and had significantly more significant mental health status than the other two.…”
Section: Discussionmentioning
confidence: 99%